2019
DOI: 10.7567/1347-4065/ab4a94
|View full text |Cite
|
Sign up to set email alerts
|

Detection of creatinine using silver nanoparticles on a poly(pyrrole) thin film-based surface plasmon resonance sensor

Abstract: Surface plasmon resonance (SPR) technique is a great tool to investigate the binding of analyte to functionalized surfaces and the immobilization of biomolecules. Creatinine is one of the biomarkers for monitoring renal functions and making a diagnosis of kidney disease. Elevated creatinine levels in the human body signifies impaired kidney disease. In this work, we developed a new strategy for creatinine detection using starch stabilized silver nanoparticles (starch-AgNPs) on poly(pyrrole) (PPy) thin film usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Pothipor et al developed a novel nonenzymatic SPR sensor for creatinine detection using starch-stabilized silver nanoparticles (starch-AgNPs) on poly(pyrrole) (PPy) Au thin film [ 57 ]. At a creatinine detection range of 0.01–1 mM, the best sensitivity was determined to be 86.3 cm −2 μ M with a LOD of 1.9 × 10 −4 mM.…”
Section: Surface Plasmon Resonance (Spr): Theory and Working Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Pothipor et al developed a novel nonenzymatic SPR sensor for creatinine detection using starch-stabilized silver nanoparticles (starch-AgNPs) on poly(pyrrole) (PPy) Au thin film [ 57 ]. At a creatinine detection range of 0.01–1 mM, the best sensitivity was determined to be 86.3 cm −2 μ M with a LOD of 1.9 × 10 −4 mM.…”
Section: Surface Plasmon Resonance (Spr): Theory and Working Principlementioning
confidence: 99%
“…In general, SPR has been used to detect a variety of targets, including glucose [ 40 42 ], uric acid [ 43 , 44 ], dopamine [ 27 , 45 , 46 ], antibody [ 47 50 ], antigen [ 47 , 51 , 52 ], salmonella [ 53 ], urea [ 43 , 54 56 ], and creatinine [ 28 , 57 , 58 ], in a variety of applications, including material characterization, medical diagnostics, food quality sensors, and drug development. Yu et al described the development of a D-shaped fiber SPR glucose biosensor with a modified MoS2-graphene composite nanostructure that exhibits approximately fourfold increased sensitivity [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, kidney failure, which affects 10% of the worldwide population, is one of the leading causes of millions of deaths every year. Notably, the functioning of the kidney is generally monitored by observing the levels of urea and creatinine biomarkers [152,153]. In this context, SPR biosensors have shown enormous potential for application in such biomarker detections.…”
Section: Analysis Of Lipid/protein Moleculesmentioning
confidence: 99%
“…Moreover, biosensors utilizing graphene-MoS2 under Kretschmann based SPR configuration have also shown promising results for urea-detection in gas chromatography and calorimetric, fluorimetric and their respective analysis [155,156]. In the case of creatinine detection, Pothipor et al [153] demonstrated an electrochemical (EC)-SPR instrumentation, with a detection limit of 0.19 µM, that used conducting-polymer based SPR sensor chip made of polypyrrole (PPy). The work involved the electropolymerization of a PPy film on the gold-coated SPR chip and subsequently monitoring the aggregation of starch-stabilized AgNPs induced by creatinine.…”
Section: Analysis Of Lipid/protein Moleculesmentioning
confidence: 99%
“…There are two approaches for exciting plasmonic waves on metal surfaces: use of a prism coupler or a grating structure. , Moreover, some research studies have used a localized surface plasma as an EC sensor. The measurement system includes a light source, a SPR sensor, stages, and a detector. The prism coupler-based system is usually more expensive than grating-based systems due to the need for precise control of the incident angle.…”
mentioning
confidence: 99%